2021
DOI: 10.7150/ijms.56142
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in carpal tunnel syndrome treated with 5% dextrose perineural injection: A retrospective study

Abstract: Background: Perineural injection therapy with 5% dextrose water (D5W) is a potential and innovative treatment with long-term efficacy for carpal tunnel syndrome (CTS). However, the prognostic factors of this management are lacking; hence, the aim of this retrospective study was to identify the prognostic factors of D5W perineural injection therapy for mild-to-moderate CTS. Methods: A total of 52 patients (52 wrists) diagnosed with mild-to-moderate CTS and treated with a single ultrasound-guided 5cc D5W perineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Likewise, the long-term effect of D5W injection has also be confirmed in Li's retrospective study in which 88.6% of 185 patients reported symptom relief more than 50% after a mean of 2.2 injections with a mean of 1–3 years' postinjection follow-up without any adverse effect [ 38 ]. Recently, Ho et al [ 40 ] reported sensory nerve conduction velocity of the MN was found to be an independent prognostic factor (odds ratio: 1.201) of poor outcome postperineural injection with D5W.…”
Section: Novel Motor-sparing Neural Injection For Ctsmentioning
confidence: 99%
“…Likewise, the long-term effect of D5W injection has also be confirmed in Li's retrospective study in which 88.6% of 185 patients reported symptom relief more than 50% after a mean of 2.2 injections with a mean of 1–3 years' postinjection follow-up without any adverse effect [ 38 ]. Recently, Ho et al [ 40 ] reported sensory nerve conduction velocity of the MN was found to be an independent prognostic factor (odds ratio: 1.201) of poor outcome postperineural injection with D5W.…”
Section: Novel Motor-sparing Neural Injection For Ctsmentioning
confidence: 99%
“…Likewise, they retrospectively found that body height and sensory nerve conduction velocity of the median nerve were risk factors for poor outcomes after PIT with D5W in patients with mild-to-moderate CTS. Moreover, the sensory nerve conduction velocity of the median nerve was found to be an independent prognostic factor of poor outcome (Ho et al, 2021). Nevertheless, the electrophysiological study presented a limited diagnosis of CTS with varied sensitivity (56% to 85%) and specificity (94% to 96%) (Witt et al, 2004; Jablecki et al, 2002).…”
Section: Perineural Injection Therapy With 5% Dextrosementioning
confidence: 99%
“…Likewise, they retrospectively found that body height and sensory nerve conduction velocity of the median nerve were risk factors for poor outcomes after PIT with D5W in patients with mild-to-moderate CTS. Moreover, the sensory nerve conduction velocity of the median nerve was found to be an independent prognostic factor (odds ratio, 1.201) of poor outcome [47]. Nevertheless, the electrophysiological study presented a limited diagnosis of CTS with varied sensitivity (56% to 85%) and specificity (94% to 96%) [48,49].…”
Section: Ctsmentioning
confidence: 99%